RAGAM SENI DAN BUDAYA MELAYU NUSANTARA PRA ISLAM - Nyayu Soraya (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2019)
Abstract: Ethnic Malays have abundant historical treasures. Flakes after fragments that are created every time form a mountain of exemplary examples and stories that have not been told. Based on regional, social and cultural aspects, Malay people inhabit a group of islands in Southeast Asia. Passion to build Malay and civilized architecture with the creation of Malay history, Malay has always been welcome with various cultural elements that enter it, but still maintains Malay flavors with their local genius as a filter. The development of Malay culture throughout the archipelago is predominantly influenced by the existence of a common similarity of identity possessed by various interactions and interrelationships. Abstrak: Etnis Melayu memiliki harta sejarah yang amat melimpah. Serpihan demi serpihan yang diciptakan setiap masanya membentuk gunung gemunung keteladanan serta kisah yang tak habis diceritakan. Berdasarkan aspek kewilayahan, sosial, dan budaya, masyarakat Melayu mendiami gugusan kepulauan di Asia Tenggara. Gairah membangun Arsitektur bermasyarakat dan berbudaya melayu mengiringi terciptanya sejarah melayu, sejak dulu melayu sudah welcome dengan berbagai unsur budaya yang masuk di dalamnya, namun tetap mempertahankan citarasa melayu dengan local jenius mereka sebagai penyaringnya. Perkembangan kebudayaan Melayu diseluruh Nusantara dominan dipengaruhi oleh adanya kesamaaan umum identitas yang dimiliki diladasi oleh berbagai interaksi dan interelasi.